Optimizing Land Dispute Resolution Through Mediation: A Legal Analysis of Biau District, Buol Regency - Moh. Ifan Ridwansyah; Nirwan Junus; Sri Nanang Meiske Kamba (Yayasan Cerdas Pedia Indonesia, 2026)
Alternative dispute resolution mechanisms in developing nations frequently experience structural dysfunctions within complex agrarian governance. This study examines the optimization of land dispute resolution through mediation in Biau District, Buol Regency. Employing a qualitative socio-legal approach, primary empirical data were gathered via purposive sampling across twenty-three key informants and analyzed rigorously using an interactive qualitative model. Grounded in Lawrence Friedman’s legal system theory, the findings reveal that mediation failures do not stem from statutory deficits, but rather from deep-seated structural pathologies, specifically uncertified local mediators, and cultural patron-client dynamics that systematically distort neutrality. Consequently, grassroots consensus frequently suffers from severe executive impotence. To resolve this procedural impasse, this article conceptualizes the Tripartite Alliance for Site Agrarian Resolution. This framework integrates local government, agrarian offices, and judicial courts via e-Court networks to transform informal settlements into legally binding settlement deeds (Acta van Dading), thereby guaranteeing absolute enforcement and sustainable agrarian justice.